On becoming a psychologist : emerging identity in education - Kullasepp, Katrin (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"On Becoming a Psychologist explores the professional identity construction of psychology students, examining their entry into the psychology profession from a socio-cultural perspective. The book brings together socio-cultural approaches and Dialogical Self Theory to gain comprehensive insight into the developmental processes behind the formation of professional identity. It conceptualises the process of becoming a psychologist as an intrapersonally and interpersonally unique semiotic process of self-regulation that unfolds through dialogical relations with the individual's socio-cultural surroundings. Building on empirical research, the book outlines the results of a longitudinal study of a cohort of psychology students throughout their studies and following their graduation. The study sheds light on how professional role expectations are negotiated between the different aspects of the self, with a particular focus on how the self is positioned throughout the course of professional education. Offering a unique perspective on the socio-cultural construction of professional identity, this book will be of great interest to scholars, researchers and graduate students in the fields of cultural psychology, applied psychology and social psychology"--
Chapter 1: Introduction: Becoming a psychologist--What does that mean? -- Chapter 2: Theoretical framework: A socio-cultural approach to professional identity construction -- Chapter 3: Introduction to the methodology of the study: Grasping the multilinear and unique developmental process over time -- Conclusion to Part I -- Chapter 4: Psychologists emerge everywhere: The academic and non-academic voices in the focus -- Chapter 5: A sign of a psychologist as an organizer -- Conclusion to Part II -- Chapter 6: Thirteen pathways to entering the professional role -- Chapter 7: The construction of professional identity through the lens of cultural psychology.
Keywords: Psychology -- Study and teaching (Higher); Students -- Social aspects; Students -- Psychology; Identity (Psychology); PSYCHOLOGY -- Social Psychology; PSYCHOLOGY -- Education & Training; PSYCHOLOGY -- Developmental -- General